Overview of Indicator Coral Fish in Poncan Islands, Sibolga, North Sumatra - Pratama, Nanda; Samiaji, Joko; Thamrin, Thamrin (Journal of Coastal and Ocean Sciences, 2021)
This study aims to determine the effect of coral reef conditions on the abundance of coral reef fish indicators of the Chaetodontidae family and to be compared descriptively. This research was conducted in February-April 2020 in Poncan Island coast, Sibolga City, North Sumatra Province. The method used in this research was a survey method, the data obtained directly on site in the form of primary data, while the secondary data was collected from the related institutions and references. The method for quantifying the number of fish used was Underwater Visual Census (UVC), for collecting data on coral reef fish indicators was using the Line Intercept Transect (LIT) method supported by SCUBA (Self Contained Underwater Breathing Apparatus). The results showed that the abundance of coral reef fish indicators for the Chaetodontidae family and coral reefs were in the average of 0-0.052 individuals/m2. The lowest abundance was found at stations 1 and 5, while the highest abundance was seen at station 2 with an average of 0.0248 individuals/m2. The abundance of live coral ranged from 5 - 51.8%. The lowest abundance was at station 1 and the highest was at station 4 with an average abundance of 30.804% which is categorized as moderate. The abundance of indicator reef fish in the waters of Poncan Island was influenced by the condition of coral reefs where in this study the abundance of live coral reefs was less than 23.02%. There was no indicator reef fish at the station